Original paperTriggering drug use in patients with psoriasis: an investigative report from Turkey - Ogretmen, Zerrin; Askin, Ulku; Hiz, Meliha Merve; Cevizci, Sibel (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: The patients clinically diagnosed with psoriasis were investigated for drug use that may trigger psoriasis. Aim: To minimize the triggering drug use and help the medical treatment of psoriasis patients. Material and methods: The study involved 289 psoriatic patients who attended our clinic in 2010–2012 and were asked to bring their drug lists of the last year, which they obtained from the pharmacy’s record system. They were advised not to use the drugs that may trigger psoriasis. Data analyses were performed using SPSS program version 19.0. Results: A total of 289 patients were included in the study. Two hundred and twenty-one patients were using non-steroidal anti-inflammatory drugs; 133 patients were using anti-reflux drugs; 35 patients were using antidiabetic drugs; 31 patients were using calcium-channel blockers and 24 patients were using β-blockers. In our study group, there was no significantly difference between median PASI scores of the patients using a triggering drug and those of who are not using a triggering drug. However, there was a positive low correlation between PASI rates and numbers of drugs used ( r = 0.180, p = 0.013). Conclusions : Many other factors may trigger psoriasis, therefore the effect of stopping or minimizing the drug use on disease remission is not known. Because of the high triggering drug use rate, it is important to enlighten psoriasis patients about triggering drugs.